Efeitos da radiação e da tempeatura em cinco acessos de pinhão manso (Jatropha curcas L.): crescimento, fluorescência da clorifila a e floração - Gasparini, Xismenia Soares da Silva (2015)
Jatrophacurcasis a promisingplantfor the production ofoil usedas biofuel. Currently, severalstudies point to thebetter understanding of thetoleranceof thisspeciesto climate changefront. Having beenportrayed asa tolerantplant tohighradiation, temperature and better productivitywheninenvironments rich inCO2. This studyaimed to analyzetheecophysiologicalbehaviorof plantsgotten by cutting, fiveaccessesof physic nutunder different conditions oftemperature andradiation andto relatethe resultswith theflowering and fruitingof these differentaccesses.Threeaccesses (here calledNEF01, NEF04 andNEF05) were obtained at the ExperimentalAreaof NOVABRABioenergyCompany,located in SãoGabrielda Palha, Espirito Santo,andtwo accesses, identified asNEF06andNEF 08, are hybridsresulting fromgenetic improvement ofBioenergyEmbrapa, propagated byseedand aregrown in theexperimental fieldof the IFES -Instituto Federal de Educação, Ciência e Tecnologia do Espírito Santo(CampusofSantaTeresa, ES).In a first experiment,the effect of thedaily variationofhighradiation andhightemperature wereanalyzed usingtransientchlorophyll afluorescence. In a second experimentthe plantswere exposedfor two weeks, the two conditionsofphotosynthetically active radiation (100% PARand 20%PAR) andits effects wereanalyzed usinggrowthparameters, the transientfluorescencechlorophyll aandreproductivephenology. The results showedthat plantsofNEF01 andNEF 05accesseswere the mostsensitive to dailyvariationsof PARandtemperatureshowingall the symptoms ofa chronicphotoinhibition.There was low efficiency in electron trappedand transport beyond primary quinone acceptor (QA) caused mainly to inactivation of the oxygen evolving complex (OEC) of PSII and of the energetic connectivity (grouping) of the PS II units (positive band K and L, respectively). An increase in initial fluorescence (F0), time (in ms) to reach the maximal fluorescence intensity (Tfmax), and the flow of energy dissipated by RC active (DI0/RC) followed by a reduction of the maximum fluorescence (Fm) were observed when radiation and increased temperatures over the day. Photosystem II (PSII) exhibited lower photochemical efficiency (fP0) and the PSI also suffered damage indicated by the lower probability with which an electron from the intersystem electron carriers is transferred to reduce end electron acceptors at the PSI acceptor side (dR0) and the 10lowest quantum yield for reductionof end electron acceptors at the PSI acceptor side (fR0).Thus, the totalperformance index(PItotal) of the plants of these twoaccesses showeda greatdecreaseanddid not returnin the evening. When subjected to 20% of photosynthetically active radiation (PAR), NEF01 had higher bud growth, greater leaf expansion and higher levels of photosynthetic pigments, though the PItotal was lower in the evaluated accesses.PlantsofNEF04 andNEF 08accesses alsoshowed a reduction inparameters indicative ofdamage toPSIIandPSIbut showeda tendency tophotosyntheticrecoveryin the late afternoon, a fact that refersto a dynamicphotoinhibition.When subjected to 20%of PAR was observed that in any of the plants of five accesses there was the formation of inflorescences. Plants of NEF 04 and NEF 08 accesses had the highest total photochemical performance index (PItotal) in both light conditions, however NEF 08 showed no formation of female flowers. Plants NEF 06 access were those that showed the best photochemical performance both throughout the day and during the exposure to two PAR conditions. There was no inhibition of the CEO or the PSII.Consequently, it has accesstohigher productivitywhen underconditionoffull sun. The results of thiswork has shownthat plantsofNEF01 andNEF05 accesseswere the mostsensitiveto high temperatures andhighradiationwhilethe plantsNEF06access would berecommendedfor cultivationin areas with highradiation andtemperatureaspresentedmechanisms totolerateclimatic changeshowinghigher photochemicaltoleranceand increased productivy